Determination of Clonazepam in Pharmaceutical Formulations by Normal and Reverse Flow Injection Analysis Coupled with Solid-Phase Reactor Containing MnO2 Immobilized - Malik H. Alaloosh Alamri (Journal of Global Pharma Technology, 2018)
Clonazepam (CLO) is an anticonvulsant agent which has hypnotic properties and widely used in the treatment epilepsy. Rapid and sensitive flow injection (FI) spectrophotometric methods are proposed for determination of CLO in pure and pharmaceutical formulations. Method (A) is normal flow injection which depend on oxidation coupling of reduced CLO with 4-methoxyphenol (MP) in presence of sodium periodate to give a colored product measured at 550 nm. While the method (B) was developed using reverse flow injection coupled with on line solid phase reactor containing MnO2 immobilized on cellulose acetate (CA) the method based on the coupling of reduced CLO with MP to give colored product which easily measured at 612 nm. The experimental conditions were optimized for both methods (A and B) and the linear range of CLO concentration was 5 – 300 and 1-250 μg.mL-1 with limits of detection of 4.312 and 0.822 μg.mL-1for methods A and B respectively. Both proposed spectrophotometric methods have been applied successfully for the determination of CLO in pure and pharmaceutical formulations.Keywords: Clonazepam, flow injection, solid phase reactor, immobilized MnO2.